Evaluasi Diri Mahasiswa Keperawatan S1 tentang Penerapan Komunikasi Terapeutik setelah Praktik Klinis - Zalukhu, Damai Zaya; Widiyarti, Sapti Heru (NUTRIX, 2026)
Therapeutic communication is a fundamental skill that nurses must possess to support the patient healing process and improve the quality of healthcare services. However, communication competence among nursing students still requires continuous evaluation, especially during clinical practice. This study aimed to describe the self-evaluation of undergraduate nursing students in applying therapeutic communication during the orientation, working, and termination phases after clinical practice. This study used a quantitative method with a descriptive design involving 75 third-year nursing students selected through purposive sampling. Data were analyzed using descriptive statistics with median values through SPSS version 26. The results showed that the implementation of therapeutic communication in all phases was categorized as good. The most dominant aspect was the use of therapeutic greetings at the beginning of the interaction (100%), while the less dominant aspects were explaining the duration of procedures and planning follow-up meetings with patients. Overall, nursing students were able to apply therapeutic communication effectively, indicating the success of clinical practice learning. The study implies that educational institutions and clinical instructors need to strengthen clinical guidance, particularly in time contracting and follow-up planning, and encourage students to conduct continuous self-reflection to improve therapeutic communication skills. Komunikasi terapeutik merupakan keterampilan dasar yang penting bagi perawat dalam mendukung proses penyembuhan pasien dan meningkatkan mutu pelayanan kesehatan, namun kompetensi komunikasi mahasiswa masih perlu dievaluasi setelah praktik klinis. Penelitian ini bertujuan mendeskripsikan evaluasi diri mahasiswa keperawatan dalam menerapkan komunikasi terapeutik pada fase orientasi, kerja, dan terminasi. Penelitian menggunakan metode kuantitatif dengan desain deskriptif terhadap 75 mahasiswa tingkat tiga yang dipilih secara purposive sampling. Data dikumpulkan menggunakan kuesioner evaluasi diri dan dianalisis dengan statistik deskriptif menggunakan nilai median. Hasil penelitian menunjukkan bahwa penerapan komunikasi terapeutik pada seluruh fase berada dalam kategori baik, dengan aspek paling dominan adalah pemberian salam terapeutik, sedangkan aspek yang masih kurang adalah penjelasan durasi tindakan dan perencanaan pertemuan lanjutan. Disimpulkan bahwa mahasiswa mampu menerapkan komunikasi terapeutik dengan baik, sehingga diperlukan penguatan bimbingan klinis dan refleksi diri berkelanjutan.